A Call to Strengthen the Law on Insanity in Kenya (Strathmore Law Review, 2017)
The legal presumption of sanity is unfortunately sometimes disproved. Indeed, there are ailments that rob some members of society the ability to be responsible moral agents. When they err, confusion arises as to how to treat the situation. The defence of insanity is the law’s response to this peculiarity. This paper, through a study of the defence, argues that the current position in Kenya needs to be reviewed and reformed, with emphasis on the need for psychiatric expertise in the process.